Effects of foliar Application with Zinc and Boron On fruitset and yield of Sweet cherry (Prunus avium L. var. Hardy Giant) - سليمان, سوسن; توكلنا, محاسن; عسكرية, عمار (Latakia University Journal -Biological Sciences Series, 2022)
This study was conducted during 2019/ 2020 on sweet cherry trees (Prunus avium L.) (Hardy Giant) cultivar planted at Sergaya- Al_Zabadani area of Rural Damascus. The experiment included 4 foliar applications: (T1: control, T2: Zn (100 ppm), T3: B (500 ppm), T4: (100 ppm Zn + 500 ppm B). Fruit set and fruit drop percentage, fruiting factor, and yield were recorded. The results showed that treatment (T4) recorded higher fruit set percentage (74.76%), fruiting factor (39.63%), and yield (20.07 kg / tree) compared to the control (9.13 kg / tree). It could be concluded that T4:(100 ppm Zn + 500 ppm B) reduced Sweet cherry fruit drop percentage (71.50%), compared to the control (80.92 %).